Biogeochemical Controls on the Relative Importance of Denitrification and Dissimilatory Nitrate Reduction to Ammonium in Estuaries. Issue 7 (16th July 2018) - Kessler, Adam J.; Roberts, Keryn L.; Bissett, Andrew; Cook, Perran L. M.
Abstract: The balance between estuarine denitrification and dissimilatory nitrate reduction to ammonium (DNRA) is critical for determining nitrogen loads received by oceans from inland waters. We aimed to determine the factors controlling the ratio between these processes and determining whether nitrogen was generally removed or recycled in estuaries. Rates of denitrification and DNRA with depth were measured in intact sediment cores in 11 estuaries along the coast of Victoria, Australia. The estuaries studied represent a range of biogeochemical conditions, land use, and catchment size. At a pore water profile scale, the ratio of denitrification to DNRA was well predicted by a multiple regression model with nitrate concentration in the overlying water, dissolved pore water iron, and ammonium as the predictor variables. Areal denitrification rates varied from 4 to 150 μmol · m −2 · hr −1, and DNRA rates varied from 2 to 30 μmol · m −2 · hr −1, with the ratio of denitrification to DNRA spanning a range from denitrification‐dominated (denitrification/DNRA = 8.4) to DNRA‐dominated (denitrification/DNRA = 0.3). DNRA dominated at sites with high iron pools and high organic carbon to nitrate ratios. We conclude that low nitrate and high Fe 2+ availability generally enhances DNRA and drives an estuary toward being N recycling, rather than N removing. Key Points: Dissolved iron and nitrate availability control the balance between denitrification and DNRA in estuaries Denitrification and DNRA rates in estuaries are of the same order of magnitude Most estuaries are slightly denitrification‐dominant